THE INFLUENCE OF EMPLOYEE PERFORMANCE ON CUSTOMER SATISFACTION AT BADAN PELAYANAN PERIZINAN TERPADU (BP2T) PONTIANAK CITY - B12111025, RIZKI AYU FITRI (Jurnal Manajemen Update, 2015)
This research aims to examine and analyze the influence of employee performance on customer satisfaction at Badan Pelayanan Perizinan Terpadu (BP2T) Pontianak City. Several measure of employee performance was analyzed including capability, attitude, and quality of work. Data collection in this research is conducted by using literature study and questionnaire for 100 samples of customers at Badan Pelayanan Perizinan Terpadu (BP2T). The research study be measured by using scale 1-4, and analyzed by using SPSS 18.0 for Windows with validity test, reliability test, customer satisfaction index, classical assumption test, , andÂ  , in order to analyze the relationship among all variables that are Capability, Attitude, Quality of Work and Customer Satisfaction. The result of the study reveals that there is a significant influence of all independent variables (capability, attitude, and quality of work) on dependent variable (customer satisfaction) proved by the result of F-Test, which Ftest = 55.851 is greater than Ftable = 2.70, ttest for capability as first independent variable (X1) is 3.161, ttest for attitude as second independent variable (X2) is 3.497, ttest for quality of work as third independent variable (X3) is 4.746, which indicate ttest for all variables is higher than ttable for df = 96 which is 1.66088, and the average of all indicators in customer satisfaction index are categorized among 2.51 â€“ 3.25 imply the indicator average value of customer satisfaction index at Badan Pelayanan Perizinan Terpadu (BP2T) Pontianak City categorized as good. The better performance of employee, then the higher level of customer satisfaction, and vice versa. Therefore Badan Pelayanan Perizinan Terpadu (BP2T) Pontianak City should improve the employee performance continuously, considering that one of government job descriptions (tasks, duties and responsibilities) is to serve the citizen as their customer. If the customer is dissatisfied with the service provided by government officer, it means that the government was failed to perform their job well. Keywords: Capability, Attitude, Quality of Work, Customer Satisfaction